Characterization of Chloroplast Protein Import without Tic56, a Component of the 1-Megadalton Translocon at the Inner Envelope Membrane of Chloroplasts - Köhler, Daniel (Plant Physiol, 2015)
We report on the characterization of Tic56, a unique component of the recently identified 1-MD translocon at the inner envelope membrane of chloroplasts (TIC) in Arabidopsis (Arabidopsis thaliana) comprising Tic20, Tic100, and Tic214. We isolated Tic56 by copurification with Tandem Affinity Purification-tagged Toc159 in the absence of precursor protein, indicating spontaneous and translocation-independent formation of the translocon at the outer envelope membrane of chloroplasts (TOC) and TIC supercomplexes. Tic56 mutant plants have an albino phenotype and are unable to grow without an external carbon source. Using specific enrichment of protein amino termini, we analyzed the tic56-1 and plastid protein import2 (toc159) mutants to assess the in vivo import capacity of plastids in mutants of an outer and inner envelope component of the anticipated TOC-TIC supercomplex. In both mutants, we observed processing of several import substrates belonging to various pathways. Our results suggest that despite the severe developmental defects, protein import into Tic56-deficient plastids is functional to a considerable degree, indicating the existence of alternative translocases at the inner envelope membrane.